The Journal of the Society for Accelerative Learning and Teaching. Volume 13, 1988 - Society for Accelerative Learning and Teaching, Inc.; Society for Accelerative Learning and Teaching, Inc. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
These four 1988 issues of the journal of the Society for Accelerated Learning and Teaching (SALT) include the following articles: "Educating the Children of Changing Cultures"; "All Stars to Center Stage: Accelerative Learning in the School of Business"; "SALT in the First Grade Classroom"; "Unlearning Technologies: Coping with Anti-Suggestive Barriers in Industry Training"; "Suggestopedia: A Suggestive-Accelerative Teaching Technique in Teaching English as a Second Language to Adult Learners"; "Effects of Relaxation Training on Verbal Ability, Sequential Thinking and Spatial Ability"; "Effects of Music-Assisted Relaxation and Mental Rehearsal Training on Acquisition of Piano Performance Skills"; "Metaphoric Teaching: The Use of Metaphor in Teaching Science and Literature"; "Use of Suggestopedia with Limited English Speaking Hispanic Elementary Students"; "Relaxation and Educational Outcomes: A Meta-Analysis"; "A Meta-Analysis of the Effects of Suggestopedia, Suggestology, Suggestive-Accelerative Learning and Teaching, and Super-Learning on Cognitive and Affective Outcomes"; "Alpha Brain Wave Formation by Sine Wave Stereo Sounds"; "Implementing Whole-Brain Methods for Reading Instruction"; "A Suggestopedia Program in Japan"; "Suggestopedia in Terms of the Second Language Acquisition/Learning Theory of Stephen Krashen"; "Effects of Guided Imagery on Basal Metabolic Rate"; "Imagery's Physiological Base: The Limbic System"; and "Learning Research Combining Cognitive Processing and Suggestopedic Variables." (MSE)
Journal of the Society for Accelerative Learning and Teaching, v13 n1-4 Spr-Win 1988.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Acceleration (Education); Adult Education; Business Administration Education; Classroom Techniques; Cognitive Development; Elementary Secondary Education; English (Second Language); Higher Education; Hispanic Americans; Imagery; Inservice Teacher Education; Instructional Effectiveness; Learning Theories; Limited English Speaking; Literature Appreciation; Metabolism; Metaphors; Program Descriptions; Reading Instruction; Relaxation Training; Science Education; Second Language Instruction; Second Language Learning; Suggestopedia; Piano Instruction; Krashen (Stephen); Reports, Evaluative; Guides, Classroom -- Teacher; Collected Works, Serials